ANALISIS MISKONSEPSI SISWA KELAS V PADA PEMBELAJARAN IPAS MELALUI METODE THREE TIER TEST DI SD NEGERI 3 KLALING - Achsa, Aldea Maulida; Fakhriyah, Fina (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2025)
This study aims to analyse the level and causes of misconceptions experienced by fifth-grade students at SD Negeri 3 Klaling in IPAS learning, particularly in the material on the human respiratory system. The study uses a qualitative approach with a diagnostic method through the Three Tier Test instrument, which consists of three levels of assessment: multiple choice, reasons for answers, and student confidence levels. The research subjects consisted of 15 students selected through saturated sampling. The results showed that 40,67% of students experienced misconceptions at a moderate level, while only 32% of students understood the concepts correctly. The highest level of misconceptions was found in question S3 (93,33%), while the lowest was in question S10 (13,33%). Factors causing misconceptions include inaccuracies in understanding basic concepts, the influence of incorrect prior knowledge, learning methods that are not contextual, a lack of visual media, low science literacy, and tricky question characteristics. These results emphasise the importance of using diagnostic assessments from the outset and concept-based learning strategies to minimize student misconceptions.